Collective Organizational Engagement to Enhance Organizational Performance: Case of Indonesia Office Services - Rulinawaty Rulinawaty; Ojat Darojat; Ajat Sudrajat (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2022)
To increase the awareness on the role of employee engagement besides the individual analysis level and a lack of studies focused on the employee’s involvement at the level of organizational, the study aims at investigating the antecedents of COE as mediating variable to increase the organizational performance. The study was conducted for 6 months to enable a deep understanding and evaluation on organizational performance. A non-purposive sampling with purpose sampling technique deployed with multi resources respondent represented organizations method (top manager, middle managers, head department and selected employee). Data analyzed for 380 respondents with Structural Equation Modeling with AMOS 22. Statistical outputs described that the green work design, OCB Organizational Resources, and Innovative Concordance Culture highly considered as the antecedent of COE in developing the organizational performance. The findings also claimed that all hypotheses proposed are accepted. This study strengthens the relationship between the COE and HRM and Enbridge the gaps existed which is informed and extended the area of field research. In another hand, this research contributed on engagement in some ways, such as extending the study on the engagement in the level of organization and provided the solutions secondly, investigating the COE as a main mechanism of the most crucial human resources. This research also developed the antecedents of COE and also highlighted how the top management could strategically increase the performance based on the organizational resources and the leverage the collective engagement continuously pursuit the strategic organizational goals.